2008
DOI: 10.1038/ncb1792
|View full text |Cite
|
Sign up to set email alerts
|

Tethering by lamin A stabilizes and targets the ING1 tumour suppressor

Abstract: ING proteins interact with core histones through their plant homeodomains (PHDs) and with histone acetyltransferase (HAT) and histone deacetylase (HDAC) complexes to alter chromatin structure. Here we identify a lamin interaction domain (LID) found only in ING proteins, through which they bind to and colocalize with lamin A. Lamin knockout (LMNA(-/-)) cells show reduced levels of ING1 that mislocalize. Ectopic lamin A expression increases ING1 levels and re-targets it to the nucleus to act as an epigenetic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 33 publications
1
83
0
Order By: Relevance
“…Similar localization of ING -3 and DAPI continued throughout the embryonic cell cycle, including during mitosis ( Figure 3B). This suggests that ING -3 is tightly bound to chromatin at all stages of the cell cycle and so differs from mammalian ING1, which is found throughout the cell during mitosis (Han et al 2008). ING -3 was also present in the gonad ( Figure 3C).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Similar localization of ING -3 and DAPI continued throughout the embryonic cell cycle, including during mitosis ( Figure 3B). This suggests that ING -3 is tightly bound to chromatin at all stages of the cell cycle and so differs from mammalian ING1, which is found throughout the cell during mitosis (Han et al 2008). ING -3 was also present in the gonad ( Figure 3C).…”
Section: Resultsmentioning
confidence: 90%
“…Comparison of the primary amino acid sequence of the ING3 proteins from different organisms showed that several regions appeared well conserved ( Figure 1A and supplemental Figure 1), including the PHD domain, the leucine zipper-like domain (LZL), the nuclear localization sequence (NLS, although it is in different locations in human and worm proteins), and the lamin interacting domain (LID, Soliman and Riabowol 2007;Han et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…ING1b also harbors three other domains: a proliferating cell nuclear antigen (PCNA) interacting protein motif (PIP) domain which binds PCNA following UV irradiation and is involved in apoptosis and cell cycle arrest, a lamin interaction domain (LID) which binds lamin A/HDAC complex to maintain its levels and biological function in the nucleus, and a partial bromodomain (PBD) which is commonly found in chromatin-associated protein [4]. Recently, it was found that serine 199 of p33…”
Section: Introductionmentioning
confidence: 99%
“…All ING proteins contain nuclear conserved region (NCR) domain, which was identified by sequence analyses and is the second most highly conserved domain in the ING family proteins [15]. This N-terminal region of ING1 has been reported to interact directly with lamin A, suggesting that the association with nuclear lamina is a common feature of this family [27]. All ING proteins contain a nuclear localization signal (NLS) at the carboxy terminal, and some of ING proteins have multiple NLS.…”
Section: Structure and Function Of Ing Family Genesmentioning
confidence: 99%